Quick and easy septoplasty: our technique - Jahan, Abdussalam Mohamed; Eldanfur, Yousef M.; Elheshani, Khaled Ahmed; Al Hanash, Basheer Ali (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Septoplasty is among the most common procedure in nasal surgery, and it has some difficulties, especially at the beginning of the surgical training. Methods: A prospective study including 154 patients underwent septoplasty surgery in Zahrawi Private Hospital using our surgical technique from October 2015 to June 2017, preoperative examination using zero degrees 3 mm sinuscope, anterior active rhinometry (AAR), and computed tomography of paranasal sinuses was done. Operative time and postoperative AAR was calculated. Results: A significant reduction in nasal breathing resistance was found in 146 patients (95%), there are two patients with postoperative bleeding, and one patient develops synechiae. No septal perforation or other major deformities. The mean septoplasty operation time was 15.34±3.66 min (range 10-35 min). Conclusions: Our surgical technique is an effective and rapid procedure for the correction of septal deformities. It is reproducible and easily learned.